Complexities of competence: A study on Finnish upper-secondary school students' lexical development and use of L2 English. A mixed-methods examination - Niitemaa, Marja-Leena (fi=Turun yliopisto|en=University of Turku|, 2024)
The dissertation examines Finnish upper-secondary school second language use from four perspectives: the development of lexical knowledge in relation to extramural activities (Article I); the role of lexical recognition in searching online sources for words and information (Article II) digitally identified cohesive features in writing (Article III); and lexical sophistication as examined by traditional lexical tests and digital analyses (Article IV). The study is situated in the context of second language acquisition with implications for teaching, and assessment building on previous research by examining lexical recognition skills across the high-, mid-, and low-frequency bands, triangulating information from questionnaires and video-observations with data elicited from traditional lexical tests and digital analyses (TAACO and TAALES). The studies in Articles I and IV were conducted longitudinally, while Articles II and III focus on examinations conducted in the second year. Article I demonstrates that using English in cognitively demanding extramural activities, such as reading and gaming, develops both overall lexical recognition skills and recognition of infrequent lexis. In the second year, these activities collectively explained 45% of the variance in the scores for infrequent lexis. Article II focused on using online sources in diverse indirect writing tasks. The results indicated that consulting online dictionaries and informational web-pages required rapid lexical recognition, multiple reading strategies and adequate digital skills to formulate queries and evaluate the search results, and that these abilities were directly associated with the participant’s lexical recognition skills. According to the analyses, participants scoring less than 60‒64% in the lexical recognition test (the VLT), did not benefit from consulting online dictionaries and other sources in diverse writing tasks. In Articles III and IV, writing skills were also examined using digital analyses. Article III investigated cohesive devices in essays written in the second year. Digital analyses (TAACO) showed that using diverse referential devices, e.g., adverbs and connectors, explained 37% of the variance in the essay ratings. In Article IV, written production was examined longitudinally using traditional lexical tests and a digital tool (TAALES). Digital analyses combining three indices (function word frequency, infrequent content words and typical English two-word combinations) collectively explained 46% in the variance of the first-essay scores and 44% of the variance in the second-essay scores. Corresponding traditional tests on associative word knowledge and recognition of two-word combinations explained 56% in the variance in the first essay scores and 61% of the second year scores. Thus, the results elicited by traditional tests were in line with the digital results. This finding implies that traditional tests for recognition and associative skills can also be used to assess lexical sophistication in language teaching.

---- Väitöskirjani tarkastelee suomalaisten lukio-opiskelijoiden englannin kielen osaamista neljästä eri näkökulmasta: miten sanoja omaksutaan vapaa-ajan harrastuksissa (Artikkeli I); kuinka hyvää sanaston tunnistamistaitoa tarvitaan digitaalisissa ympäristöissä (Artikkeli II); mitä kielellisiä keinoja käytetään johdonmukaisesti etenevän ja lukijaystävällisen tekstin tuottamiseen digitaalisen analyysin perusteella (Artikkeli III); miten monipuolista ja tekstilajiin sopivaa sanastoa kirjoitelmat sisältävät perinteisten sanastotestien ja digitaalisen analyysin valossa (Artikkeli IV). Osana vieraan kielen omaksumisen tutkimusta väitöskirja tarjoaa sovelluksia opetukseen ja arviointiin ja laajentaa tietoa englannin kielen osaamisesta testaamalla myös harvinaisten sanojen tunnistamista yhdistäen määrällisiä ja laadullisia menetelmiä sekä vertailemalla digitaalisten analyysien (TAACO ja TAALES) sekä perinteisten testien tuloksia. Artikkelit I ja IV ovat pitkittäistutkimuksia, kun taas Artikkelit II ja III tarkastelevat testisuorituksia lukion kakkosvuonna. Artikkeli I osoittaa, että kognitiivisesti vaativat harrastukset kuten englannin käyttö lukiessa ja videopelejä pelatessa kehittävät harvinaisten sanojen merkitysten tunnistamista. Tilastollisessa analyysissä nämä harrastukset selittivät 45 % harvinaisten sanojen tunnistamisen varianssista toisena opiskeluvuonna. Artikkeli II todistaa, että verkkosanakirjojen käyttö ja tiedonhaku Internetissä vaativat käyttäjältä nopeaa merkitysten ymmärtämistä, monipuolisia luku- ja tiedonhakutaitoja sekä kykyä arvioida hakutuloksia kriittisesti. Analyysien mukaan sanaston tunnistustestissä (VLT) pitäisi onnistumisprosentin olla 60 %‒64 %, jotta sanakirjojen ja lähteiden käyttö tuottaisi tulosta. Artikkeleissa III ja IV tutkittiin lukiolaisten kirjoitustaitoja englannin kielessä myös digitaalisten analyysien avulla. Artikkeli III tarkasteli tyypillisiä koheesiokeinoja englannin kirjoitelmissa toisena opiskeluvuonna. Digitaalinen analyysi (TAACO) osoitti, että taitavasti laadittujen tekstien sidosteisuus perustui pääasiassa adverbien ja konjunktioiden monipuoliseen käyttöön eli kykyyn organisoida tekstiä. Nämä piirteet selittivät 37 % kirjoitelmien arvosanojen varianssista. Artikkeli IV tarkasteli kahtena vuonna laadittuja kirjoitelmia perinteisin testein ja digitaalisen työkalun avulla (TAALES). Regressioanalyysissa kolmen piirteen yhdistelmä (adverbit, apuverbit, konjunktiot; harvinaiset sisältösanat; tavalliset kollokaatiot) selitti 46 % ensimmäisten kirjoitelmien arvosanojen varianssista ja toisena vuonna 44 %. Verrattaessa kirjoitelmien arvosanoja vastaavien perinteisten testien tuloksiin, assosiaatioiden tuottaminen ja sanayhdistelmien tunnistus selittivät 56 % kirjoitelmien arvosanojen varianssista ensimmäisenä vuonna ja 61 % toisena vuonna. Digitaalisten ja perinteisten analyysien tulokset olivat siis samansuuntaiset. Tulokset osoittavat, että perinteiset sanaston tunnistus- ja yhdistelytehtävät sopivat myös vaativan sanaston käytön arviointiin kielenopetuksessa.